Penilaian Autentik pada Pembelajaran Pendidikan Agama Islam (PAI) di Sekolah dan Perguruan Tinggi - Anis Marfuah; Febriza Febriza (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2019)
Changes in education in Indonesia in the form of one form of and also a new curriculum that serves as a refinement of the previous curriculum, namely KTSP. The method of this study is to use literature research (literature research) to be analyzed and concluded. The results of this study are discussing the notion of authentic assessment, the characteristics of authentic assessment, comparison of authentic and non-authentic assessment, authentic assessment principles, techniques and instrumens, authentic assessment components, and the problems of implementing authentic assessment in schools and in universities. Conclusion Authentic assessment techniques pay attention to 3 things namely affective, cognitive, and psychomotor competencies. The component of authentic assessment itself that needs attention is the preparation of authentic assignments and the rubric for authentic assessment. While the Probematics of the implementation of authentic assessment in schools or in college each school and college has different obstacles.